Molecular diversity study in advanced early maturing lines of rice using RAPD technique - Ershad, HM; Begum, SN; Khalil, MI; Islam, MM (Bangladesh Journal of Agricultural Research, 2018)
Abstract not available Bangladesh J. Agril. Res. 43(1): 169-173, March 2018